Governance in Europe: insights from a survey among actors involved in local state-society relations - Heinelt, Hubert (Anuario de Derecho Municipal, 2023)
This article presents results of an empirical study on local governance in a number of European countries carried out by a group of scholars who has conducted surveys of various local political actors for many years. The results of these studies, which have been published in two books, will be assessed with regard to central questions of the governance debate. These include, among other things, questions of the understanding of democracy as well as the representational claims of the social actors involved. Moreover, it is emphasised that surveys are central to finding out how actors assess institutional conditions under which they have to act, i.?e. how they perceive institutional opportunities and limitations for their political choices.